Safety and Efficacy of Chop for Treatment of Diffuse Large B-Cell Lymphoma with Different Combination Antiretroviral Therapy Regimens: Sculpt Study. Issue 5 (July 2013) - Wong, Alison YJ; Marcotte, Suzanne; Laroche, Mathieu; Sheehan, Nancy L; Kukreti, Vishal; Routy, Jean-Pierre; Lemieux, Bernard; Seki, Jack T; Rouleau, Danielle; Tseng, Alice
Background: Use of combination antiretroviral therapy (cART) and cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) with or without rituximab for treatment of diffuse large B-cell lymphoma (DLBCL) in HIV substantially increases response rates but may also increase toxicity, possibly due to antiretroviral– antineoplastic drug interactions. The objective of this study was to evaluate the frequency of complete remission (CR) of DLBCL in patients treated with CHOP while receiving a protease inhibitor (PI) versus a non-PI-based cART. Methods: A retrospective multicentre pilot study was conducted in HIV-infected patients on cART treated for DLBCL with CHOP between 2002–2010 in three academic hospitals. Results: A total of 34 patients were included with 65% and 35% of patients receiving a PI and non-PI-based cART, respectively. Baseline characteristics between groups were similar; overall 85% were male, median age was 43 years, 50% had an International Prognostic Index (IPI) of 2–3 and median CD4 + T-cell count was 225 cells/mm 3 . CR was achieved in 77% and 58% of patients in the PI and non-PI groups, respectively ( P =0.21), with 65% and 63% of patients achieving 2-year overall survival ( P =1.00). A multivariate analysis showed that lower IPI score alone was significantly associated with higher CR rates ( P =0.05). Toxicity was similar between both groups. Conclusions: Similar efficacy and toxicity of CHOP was observed in patients receiving a PI and non-PI-based cART.